No changes in heme synthesis in human Friedreich's ataxia erythroid progenitor cells - Steinkellner, Hannes; Muckenthaler, Martina (Gene, 2017)
Friedreich's ataxia (FRDA) is a neurodegenerative disease caused by reduced expression of the protein frataxin. Frataxin is thought to play a role in iron-sulfur cluster biogenesis and heme synthesis. In this study, we used erythroid progenitor stem cells obtained from FRDA patients and healthy donors to investigate the putative role, if any, of frataxin deficiency in heme synthesis. We used electrochemiluminescence and qRT-PCR for frataxin protein and mRNA quantification. We used atomic absorption spectrophotometry for iron levels and a photometric assay for hemoglobin levels. Protoporphyrin IX and Ferrochelatase were analyzed using auto-fluorescence. An “IronChip” microarray analysis followed by a protein-protein interaction analysis was performed. FRDA patient cells showed no significant changes in iron levels, hemoglobin synthesis, protoporphyrin IX levels, and ferrochelatase activity. Microarray analysis presented 11 genes that were significantly changed in all patients compared to controls. The genes are especially involved in oxidative stress, iron homeostasis and angiogenesis. The mystery about the involvement of frataxin on iron metabolism raises the question why frataxin deficiency in primary FRDA cells did not lead to changes in biochemical parameters of heme synthesis. It seems that alternative pathways can circumvent the impact of frataxin deficiency on heme synthesis. We show for the first time in primary FRDA patient cells that reduced frataxin levels are still sufficient for heme synthesis and possibly other mechanisms can overcome reduced frataxin levels in this process. Our data strongly support the fact that so far no anemia in FRDA patients was reported.
Gesehen am 19.09.2018